Application of three-dimensional visualization technology in phacoemulsification benefits the dry eye symptoms of patients after cataract surgery - Wu, Chen; Chen, Qingzhong; Zhang, Guangbin (Frontiers in Medicine, 2024)
To investigate the effects of the three-dimension visualization system on dry eye in patients after cataract phacoemulsification.Methods: Seventy-one patients (104 eyes) were enrolled in this study and assigned to the conventional microscopic group (CM group) or threedimension group (3D group). Ocular Surface Disease Index, The Schirmer I test (SIt), lipid layer thickness (LLT), noninvasive tear breakup time (NIBUT) and other factors associated with dry eye were recorded before and 1 week and 1 mouth after surgery. The operation time and intraoperative light intensity (ILI) were also recorded.The ILI in the 3D group was significantly lower than that in the CM group (33% vs 60%, P < 0.01). There was an interaction (group and time) effect for first NIBUT (NIBUT-F), average NIBUT (NIBUT-Ave), tear meniscus height (TMH) and the score of eye redness (P interaction <0.05).The main effects of group on SIt, LLT, NIBUT-F, NIBUT-Ave and the score of eye redness were significant (P group < 0.05). In the CM group, SIt, LLT, NIBUT-F, NIBUT-Ave, TMH were lower than those of the 3D group, the score of eye redness was higher than that of the 3D group at 1 week and 1 month after surgery (all P < 0.05). The changes in NIBUT-F and NIBUT-Ave between before surgery and 1 week after surgery showed negative correlations with ILI (P < 0.01).Compared with microscopic surgery, the 3D visualization system can provide better tear film stability for patients after cataract surgery.